Highly efficient hydrogen production through ethanol photoreforming by a carbon nanocone/Pd@TiO2 hybrid catalyst. Issue 4 (16th November 2015) - Melchionna, M.; Beltram, A.; Montini, T.; Monai, M.; Nasi, L.; Fornasiero, P.; Prato, M.
Abstract : Production of molecular hydrogen (H2 ) is becoming an increasingly prominent process, due to the high expectations as a new green energy carrier and key reagent for many industrial processes. Abstract : Production of molecular hydrogen (H2 ) is becoming an increasingly prominent process, due to high expectations as a new green energy carrier and key reagent for many industrial processes. Herein we report the high efficiency of H2 production via photoreforming of ethanol using a catalyst based on hierarchical carbon nanocones hybridised with an inorganic layer of nanocrystalline TiO2 containing Pd nanoparticles.